Development of integrated electrochemical-quartz crystal microbalance biosensor arrays: towards ultrasensitive, multiplexed and rapid point-of-care dengue detection - Zainuddin, Ahmad Anwar; Nordin, Anis Nurashikin; Asri, Mohd Afiq; Ab Rahim, Rosminazuin; Guines, Cyril; Chatras, Matthieu; Pothier, Arnaud; Mak, Wing Cheung (SciTePress, 2019)
Dengue is an infectious mosquito-borne viral disease that affects approximately 50 million people annually worldwide and is prevalent mostly in the tropics. Severe cases of dengue can be fatal, making early detection and fast diagnosis crucial towards improving patient care and survival rates. Currently, early detection can be achieved through detection of NS1 protein, using ELISA technique. Unfortunately, ELISA is an expensive method, making it unsuitable as a screening technique, especially in low-resource settings. In this work, we present a prototype device and its early validation studies, of an integrated electrochemical and mass-sensor for dengue NS1 antigen. The sensor is connected to open source mass-sensing software and hardware, OpenQCM which makes it easily portable. Having dual-measurement capabilities (mass and impedance) increases the sensitivity of the sensor. Preliminary studies suggest that the prototype could achieve ultralow limit of detection as low as 10 ng mL-1, dual-sensing cross-validation capability, portable size, sample-toanalysis time of less than 30 minutes, and parallelization of multiple assays. This work could lead to early and accurate dengue detection in routine point-of-care settings.